Transition metal- and organophotocatalyst-free perfluoroalkylation reaction of amino(hetero) aromatics initiated by the complex [(TMEDA)I$I3] and visible light - Yerien, Damián Emilio (2016)
Radical initiation for the perfluoroalkylation reaction of amino(hetero)aromatics has been accomplishedemploying the complex [(TMEDA)I$I3] and visible light. This methodology circumvents the use ofmetal(organo)catalysts and biologically-relevant substrates are easily substituted with RF moieties employinga mild and environmentally benign radical strategy starting from readily-available perfluoroalkyl iodides RFI.